Construction of Ustadz Firanda Andirja Abidin's Da'wah on Youtube Account about Tahlilan - Saniatul Hidayah (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2024)
This paper will discuss the construction of tahlilan through da'wah from the Youtube account